ZONASI PEMANFAATAN LAHAN KECAMATAN PACIRAN TERKAIT RENCANA KAWASAN EKONOMI KHUSUS (KEK) INDUSTRI MARITIM - S Surjono; Saura Olivia Effendy; Eddi Basuki Kurniawan (TATALOKA, 2011)
The Special Economic Zones for Maritime Industries in Paciran District would create a new activity center in North Lamongan. Indications of rapid development in the northern of Lamongan Region made this district strategic in spatial and economic context, however there was no policy of Lamongan Local Government to regulate land use and control land use development in the Paciran District related to the Economic Zone. The purpose of this study were to identify the characteristics and development of land use in Paciran District Year 1999-2010, to analyze the physical potency and constraints of land and provide land-use zoning recommendations in Paciran district related to the planning of Maritime IndustriesSpecial Economic Zones. Descriptive analysis aimed to identify the characteristics and development of land use, evaluative descriptive analysis was used to evaluate the land policy, the the physical potency and constraints of land and land suitability. Evaluative analysis was used to determine the need for housing land and facilities. Prescriptive analysis was used to determine land use zoning. The results of this study showed that the development of land use in Paciran District was still dominated by unbuilt area, so it has great potentialstodevelopindustrial estates. Based on the analysis, Paciran District should be divided into 13 blocks. For zoningrecommendations, Paciran District was divided into seven main zones, they were: the zone of protected areas, agriculture zone, residential zone, industrial zone, mining zone, forest zone and tourism zone. Zoning of industrial land in Paciran District related to the planning of KEK will be directed to the development of shipyard maritime industries in the village of Kemantren (Block 10) and Sidokelar (Block 11), which covers an area of 540.57 hectares.